Are there Age‐Related Differences in the Effects of Prior Knowledge on Learning? Insights Gained from the Memory Congruency Effect. Issue 2 (5th April 2022) - Brod, Garvin; Shing, Yee Lee
ABSTRACT: Humans accumulate knowledge throughout their entire lives. In what ways does this accumulation of knowledge influence learning of new information? Are there age‐related differences in the way prior knowledge is leveraged for remembering new information? We review studies that have investigated these questions, focusing on those that have used the memory congruency effect, which provides a quantitative measure of memory advantage because of prior knowledge. Regarding the first question, evidence suggests that the accumulation of knowledge is a key factor promoting the development of memory across childhood and counteracting some of the decline in older age. Regarding the second question, evidence suggests that, if available knowledge is controlled for, age‐related differences in the memory congruency effect largely disappear. These results point to an age‐invariance in the way prior knowledge is leveraged for learning new information. Research on neural mechanisms and implications for application are discussed. LAY ABSTRACT: Prior knowledge shapes the way we learn. At first glance, the influence of prior knowledge on learning, as measured by memory congruency effects, increases with age. However, when controlling for the amount of prior knowledge, the age‐related increase shrinks or even disappears altogether, suggesting that knowledge is similarly used to form new memories across the lifespan. Children and older adults, however, are more likely to falsely endorse knowledge‐congruent information, underscoring the double‐edged role of knowledge.